Asabiyah and Social Inequality in the Digital Age: An Ibn Khaldunian Perspective on TikTok Culture in Indonesia - Fanani, Ahmad Farid; Iswahyudi, Teguh; Zakaria, Muhammad Fadhlurrahman; Pratomo, Herdianto Wahyu (Jurnal Adabiyah, 2025)
Indonesia's significant social inequality is increasingly visualized in viral trends on TikTok, moving from statistical reality to digital performance. This research analyzes this digital phenomenon through the lens of Ibn Khaldun's concepts of asabiyah (social cohesion) and umran (civilization). Its significance lies in bridging contemporary digital media studies rarely utilize classical Islamic sociological theory, and conversely, Khaldunian analysis has not been systematically applied to digital-age inequality. The research employs a qualitative method, integrating digital content analysis of selected TikTok videos depicting educational, employment, and wealth disparities with a theoretical library analysis of Ibn Khaldun's framework. Findings reveal that these viral visuals are not mere entertainment but reflect a fragmented society. This fragmentation, characterized by status hierarchies and vast economic gaps, is symptomatic of the erosion of social asabiyah. The research argues this aligns with Ibn Khaldun’s description of the 'asr al-da‘f (phase of decline) in a civilizational cycle. This research contributes a novel theoretical lens for digital media studies, demonstrating that classical sociology can interpret digital content as a reflection of deep structural disruptions, not just as entertainment. ملخص صبحت الفجوة الاجتماعية في إندونيسيا تُعرض بشكلٍ متزايد من خلال الاتجاهات المنتشرة على منصة "تيك توك"، حيث تتحوّل الأرقام والإحصاءات إلى مشاهد رقمية. تتناول هذه الدراسة هذا الظاهرة من منظور فكر ابن خلدون، وخصوصًا مفهومي العصبية (التضامن الاجتماعي) والعمران (الحضارة). تكمن أهمية هذه الدراسة في سعيها لربط دراسات وسائل الإعلام الرقمية المعاصرة بنظريات علم الاجتماع الإسلامي الكلاسيكية التي نادرًا ما تُستخدم، بينما لم يُطبَّق تحليل ابن خلدون بشكل منهجي لفهم عدم المساواة في العصر الرقمي. تعتمد الدراسة على المنهج النوعي من خلال تحليل محتوى مجموعة من مقاطع الفيديو في "تيك توك" التي تُظهر الفوارق في التعليم والعمل والثروة، مع الاستناد إلى تحليل مكتبي لأفكار ابن خلدون. وتُظهر النتائج أن هذه المقاطع المنتشرة ليست مجرد ترفيه، بل تعكس مجتمعًا منقسمًا ومتباعدًا اجتماعيًا. وتُعدّ هذه الحالة دليلاً على ضعف العصبية أو روح التضامن، كما وصفها ابن خلدون في مرحلة تراجع الحضارة. وتُقدّم هذه الدراسة منظورًا جديدًا لفهم وسائل الإعلام الرقمية، مبينةً أن المحتوى الترفيهي في ظاهره قد يكشف عن مشكلات اجتماعية أعمق Abstrak Kesenjangan sosial di Indonesia kini semakin sering terlihat melalui tren viral di TikTok, yang mengubah data dan angka menjadi tontonan digital. Penelitian ini membahas fenomena tersebut dengan menggunakan pemikiran Ibn Khaldun, khususnya konsep asabiyah (kebersamaan sosial) dan umran (peradaban). Penelitian ini penting karena berusaha menghubungkan kajian media digital masa kini dengan teori sosiologi Islam klasik yang jarang digunakan, sementara pemikiran Ibn Khaldun sendiri belum banyak diterapkan untuk membaca ketimpangan sosial di era digital. Metode yang digunakan adalah kualitatif, dengan menganalisis konten beberapa video TikTok yang menampilkan perbedaan dalam pendidikan, pekerjaan, dan kekayaan, serta dikaitkan dengan kajian pustaka tentang teori Ibn Khaldun. Hasil penelitian menunjukkan bahwa konten viral tersebut bukan sekadar hiburan, tetapi mencerminkan masyarakat yang terpecah dan penuh jarak sosial. Kondisi ini menandakan melemahnya asabiyah atau rasa kebersamaan dalam masyarakat, sebagaimana digambarkan Ibn Khaldun dalam masa kemunduran peradaban. Penelitian ini memberikan cara pandang baru dalam memahami media digital, bahwa konten yang tampak ringan sebenarnya menggambarkan persoalan sosial yang lebih dalam.